Design and Fabrication of a Mini Refrigerator Using a Peltier Thermoelectric Module - Okorie, George Aleje; Faci, Nunaya David; Okorie, Patrick Ubeh (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2023)
A mini thermoelectric Peltier Refrigerator was designed and built in this study. The Peltier thermoelectric cell was attached in between an external heat sink and internal radiator that acted to remove heat from the internal space of refrigeration box to be conducted and removed to the ambient. To ensure the success of this study several criterions are to be satisfied such as portability, size and cost of the system. The design of the system is based on the principles of thermoelectric module (i.e. Peltier effect) to create a hot side and a cold side. Thermoelectric refrigeration work on the principle of see beck effect in which the voltage is applied between two different combinations of metal and due to effect of see beck the cooling and heating phenomena happens which can be used accordingly for different purposes. The cold side of the thermoelectric module is used for refrigeration purposes; provide cooling to the vaccine chamber. On the other hand, the heat from the hot side of the module is rejected to the surroundings with the help of a heat sink and fan assembly.